Synthesis of Schiff Bases of 4-Amino-5- (2-Hydroxyphenyl)-4H- 1,2,4-Triazole-3-Thiol as Potent Antimicrobial Agents - Kapri, Kamal Prasad; Singar, Som Bahadur; Khanal, Santosh; Shakya, Bhusan (Amrit Research Journal, 2020)
In recent years, the emergence and rapid spread of multidrug-resistant microbes are increasingly becoming major concerns for public health because infections from such pathogens lead to higher mortality imposing huge healthcare costs. With the currently available drugs becoming ineffective due to the drug resistance developed by pathogens, the synthesis of more powerful antimicrobial agents with a broad spectrum of activity has become a crucial need for the treatment of microbial infections. Some new amino-substituted Schiff bases with triazole ring (4a-c) were prepared by cyclization of potassium 2-(2-hydroxybenzoyl) hydrazinecarbodithioate (2) with hydrazine hydrate followed by condensation with aromatic aldehydes. The newly synthesized compounds were characterized by spectral techniques like FTIR, 1H-NMR, and 13C-NMR. Antimicrobial screening of the synthesized compounds revealed that they possess good to moderate activities against a variety of microorganisms.